2021
DOI: 10.21203/rs.3.rs-224753/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Outcomes in Patients Undergoing B Cell Depletion Therapy and Those With Humoral Immunodeficiency States: A Scoping Review

Abstract: The role of humoral immunity has been well established in reducing infection risk and facilitating viral clearance in patients with COVID-19. However, the relationship between specific antibody responses and severity of COVID-19 is less well understood. To address this question and identify gaps in knowledge, we utilized the methodology of a scoping review to interrogate risk of infection and clinical outcomes of COVID-19 in patients with iatrogenic and inborn humoral immunodeficiency states based on existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(77 reference statements)
1
6
0
1
Order By: Relevance
“…An H-score calculated afterwards estimated a 95.5% probability of HLH [2]. In accordance with the available literature, B-cell depletion, dysregulated humoral immunity and a high H-score are independent predictors of mortality in COVID-19, which elucidate the unfavorable prognosis in our patient [3,4]. In contrast, the researchers have recently underlined that there is lack of association between level of SARS-CoV-2 neutralizing antibodies as a single parameter and severity of the disease [5].…”
supporting
confidence: 85%
“…An H-score calculated afterwards estimated a 95.5% probability of HLH [2]. In accordance with the available literature, B-cell depletion, dysregulated humoral immunity and a high H-score are independent predictors of mortality in COVID-19, which elucidate the unfavorable prognosis in our patient [3,4]. In contrast, the researchers have recently underlined that there is lack of association between level of SARS-CoV-2 neutralizing antibodies as a single parameter and severity of the disease [5].…”
supporting
confidence: 85%
“…[25][26][27][28][29] More recently studies have reported unfavorable prognosis particularly in those with shorter duration between last rituximab infusion and infection. [30][31][32][33] These conflicting results may reflect heterogeneity in the diseases treated with rituximab, intensity of B cell depletion and IgG levels at infection onset and number of previous treatments. Similarly, the data regarding calcineurin inhibitors has been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…While patients with IMIDs on BCDTs have been recognized to be vulnerable to severe COVID-19 infections, 3,4,6,7 relatively scant data exist regarding their risks for and outcomes of breakthrough infections 2,18 . The current cohort of breakthrough patients consisted of nearly equal numbers of patients with rheumatic and neuro-inflammatory disease and most (91.9%) were either fully vaccinated or boosted, with only 6 (8.1%) with incomplete vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…While there is great heterogeneity in the capacity of specific immunosuppressive agents to limit the integrated immune response to both natural infection as well as vaccines, of particular concern is the class of B cell depleting therapies (BCDTs) widely used to treat an array of IMIDs. Before the introduction of vaccines, treatment of both rheumatic and neurologic IMIDs with such BCDTs was associated with more severe COVID-19 [3][4][5][6][7][8][9] . Furthermore, numerous studies have documented the capacity for BCDTs such as rituximab and ocrelizumab to profoundly impair humoral response to numerous vaccines including SARS-CoV-2 [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%